Ostanki zgodnjerimskih zidanih struktur na Serminu - Gaspari, Andrej (Annales. Series historia et sociologia, 1998)
The dominant and strategically important site of the Sermin hill at the outlet of the Rižana river into the sea has, according to the so far existing findings, strongly influenced the human settling since the Neolithic. Our knowledge of the archaeological traces of the past events is connected especially with the lively constructional activity in the past decades, which has marked the image of Sermin and has at the same time made it possible to have at least a partial insight into its earth layers. During this year's field survey trenching in the southwestern part of the Sermin hill we discovered some very important remains of the Early Roman built structures, which were accompanied by rather numerously modest artefacts of small material culture ...
Keywords: 1997; archaeology; arheologija; arheološka izkopavanja; arheološke najdbe; Koper; Sermin